Peran Penyiaran Islam dalam Meningkatkan Kesadaran Kesehatan Mental Remaja - Fuadi, Muhamad Hanif; Ramadhanita, Frista Fitriany (PT. Cahya Edupreneur Indonesia, 2024)
This article discusses the role of Islamic broadcasting in increasing mental health awareness among adolescents through community service activities at Madrasah Aliyah Swasta Cilendek, Tasikmalaya City. The methods used include workshops, group discussions, and group counseling. The results showed an increase in participants' understanding of mental health, Islamic values that support mental health, and the role of Islamic broadcasting media in spreading positive information. This activity also succeeded in reducing stigma related to mental health problems and encouraging adolescents to play an active role in maintaining their mental health.